DIRECTORS’ DUTY AND LIABILITY IN INSOLVENT TRADING - Shereen Khan; Nasreen Khan; Olivia Tan Swee Leng (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The effect of the novel coronavirus (Covid-19) pandemic has resulted in current and future liquidity, balance sheet, and cash flow problems. There is an anticipated decline in the profitability of the businesses during this uncertain period and attention has been turned to the directors’ ‘duties and liabilities’ to creditors when the company is on the verge of insolvency. Directors have to strike a balance among the shareholders, creditors, and workers in the corporate restructuring process. In engaging with these stakeholders during the transformation process, the directors play a key role. It is about quick choices and decisions to be taken to save a business on the verge of insolvency, and it is therefore vital that directors act at the first sign of financial distress. There is a general duty for directors not to trade when insolvent or close to the point of insolvency. Directors also have a contractual obligation to avoid insolvent trading. This article discusses the duties of directors under the Companies Act 2016 (CA 2016) to avoid insolvent trading. It further discusses by analysing based on the comparative study with other selected jurisdictions. This article proposes that while it is important to protect creditors’ interest by making the directors personally liable for insolvent trading, for the best interest of all stakeholders, there should be a balance between the security of creditors and the rescue of the company.